0.18 um CMOS Power Amplifier for 2.45 GHz IoT Application - Ang, Wei Keat (Universiti Sains Malaysia, 2018)
Due to the emerging of the Internet of Things (IoT) industry in recent years, the demand for the higher integration of wireless communication system with higher data rate of transmission capacity and lower power consumption has increases tremendously. The design of Radio Frequency (RF) Power Amplifier (PA) is getting more challenging and crucial. In this work, a 0.18 um CMOS PA for 2.45 GHz IoT application is presented. The designed PA consists of two stages, which are the driver stage and output stage. Both driver stage and output stage utilise single stage common source transistor configuration. In the view of performance, the PA is able to deliver more than 20 dB gain in the frequency range of 2.4 GHz to 2.5 GHz. The maximum output power achieved by PA is 13.44 dBm. As the PA designed is targeted for Bluetooth Low Energy (BLE) transmitter, a minimum of 10 dBm output power should be achieved by PA to transmit the signal in BLE standard. The PA exhibits a nearly constant Third-order Output Intercept Point (OIP3) of 18 dBm before PA goes into saturated after 10 dBm output power. The PA shows a peak Power Added Efficiency (PAE) of 17.61 % at 13.24 dBm output power. Therefore, the designed PA exhibits good linearity up to 10 dBm output power without sacrificing much on the efficiency. At the operating frequency of 2.45 GHz, the PA exhibits stability k-factor,